Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior, Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models, Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior, Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon

Sharing of potential nest sites by Etheostoma olmstedi males suggests mutual tolerance in an alloparental species. - Stiver, Kelly A; Wolff, Stephen H; Alonzo, Suzanne H (PloS one, 2013)
When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and individuals could have each occupied a potential nest site without same-sex sharing. Males were more likely to share a nest site with one other when the difference in size between them was larger rather than smaller. There was no evidence that female sharing was dependent on their relative size. Fish were generally more likely to use and share larger sites, in accordance with the greater relative surface area they offered. We discuss how one or both sharing males may potentially benefit, and how male sharing of potential nest sites could relate to female mating preferences. Tessellated darter males are known to provide alloparental care for eggs but this occurs without any social contact between the alloparent and the genetic father of the young. Thus, the suggestion that they may also share sites and maintain social contact with reproductive competitors highlights the importance of increased focus on the potential complexity of reproductive systems.
Keywords: *Behavior, Animal; *Nesting Behavior; *Perches/ph [Physiology]; *Reproduction; Animals; Behavior, Animal; Etheostoma olmstedi; Female; Male; Nesting Behavior; Perches; Reproduction; Sexual Behavior, Animal; animal behavior; article; competitor species; controlled study; dept.psy; female; fish; male; male animal; mate choice; nesting; nonhuman; peer-reviewed; population density; population size; sex difference; social behavior; symbiosis

Conflict and cooperation in male–male partnerships alter paternal care behavior in the ocellated wrasse - Hellmann, Jennifer; Stiver, Kelly; Marsh‐Rollo, Susan; Alonzo, Suzanne (Behavioral Ecology, 2025)
Keywords: Biology; Fish; Fishery; Genetics; Paternal care; Symphodus ocellatus; Wrasse; Zoology; dept.psy; parental care; plasticity; reproduction; sexual selection; temperature

Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Animal Behaviour, 2019)
Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. © 2019 The Association for the Study of Animal Behaviour
Keywords: Symphodus ocellatus; Vertebrata; arginine vasotocin; behavioral response; dept.psy; fitness; fitness consequences; life history; nonapeptide; parental care; parental investment; paternal care; peer-reviewed; peptide; phenotype; phenotypic engineering; physiological manipulation; physiology; proximate mechanisms; reproductive cost; reproductive investment; reproductive success; trade-off; trade-offs; wild population

Ovarian fluid allows directional cryptic female choice despite external fertilization. - Alonzo, Suzanne H; Stiver, Kelly A; Marsh-Rollo, Susan E (Nature Communications, 2016)
In species with internal fertilization, females can favour certain males over others, not only before mating but also within the female's reproductive tract after mating. Here, we ask whether such directional post-mating (that is, cryptic) female mate choice can also occur in species with external fertilization. Using an in vitro sperm competition experiment, we demonstrate that female ovarian fluid (ovarian fluid) changes the outcome of sperm competition by decreasing the importance of sperm number thereby increasing the relative importance of sperm velocity. We further show that ovarian fluid does not differentially affect sperm from alternative male phenotypes, but generally enhances sperm velocity, motility, straightness and chemoattraction. Under natural conditions, female ovarian fluid likely increases the paternity of the preferred parental male phenotype, as these males release fewer but faster sperm. These results imply females have greater control over fertilization and potential to exert selection on males in species with external fertilization than previously thought possible.
Keywords: *Body Fluids/me [Metabolism]; *Choice Behavior/ph [Physiology]; *Fertilization/ph [Physiology]; *Ovary/me [Metabolism]; *Spermatozoa/ph [Physiology]; Animals; Body Fluids; Choice Behavior; Female; Fertilization; Male; Ovary; Perciformes; Perciformes/ph [Physiology]; Reproduction; Reproduction/ph [Physiology]; Sexual Behavior, Animal; Sexual Behavior, Animal/ph [Physiology]; Sperm Count; Spermatozoa; animal; body fluid; decision making; dept.psy; experimental study; female; fertilization; fertilization (reproduction); in vitro study; liquid; male; mate choice; metabolism; ovary; paternity; phenotype; physiology; reproduction; sexual behavior; species; sperm; sperm competition; spermatozoon; spermatozoon count; spermatozoon motility; thinking

Experimentally induced variation in neuroendocrine processes affects male reproductive behaviour, sperm characteristics and social interactions - Nugent, Bridget M.; Stiver, Kelly A.; Hofmann, Hans A.; Alonzo, Suzanne H. (Molecular Ecology, 2019)
While extensive research has focused on how social interactions evolve, the fitness consequences of the neuroendocrine mechanisms underlying these interactions have rarely been documented, especially in the wild. Here, we measure how the neuroendocrine mechanisms underlying male behaviour affect mating success and sperm competition in the ocellated wrasse (Symphodus ocellatus). In this species, males exhibit three alternative reproductive types. “Nesting males” provide parental care, defend territories and form cooperative associations with unrelated “satellites,” who cheat by sneaking fertilizations but help by reducing sperm competition from “sneakers” who do not cooperate or provide care. To measure the fitness consequences of the mechanisms underlying these social interactions, we used “phenotypic engineering” that involved administering an androgen receptor antagonist (flutamide) to wild, free-living fish. Nesting males treated with flutamide shifted their aggression from sneakers to satellite males and experienced decreased submissiveness by sneaker males (which correlated with decreased nesting male mating success). The preoptic area (POA), a region controlling male reproductive behaviours, exhibited dramatic down-regulation of androgen receptor (AR) and vasotocin 1a receptor (V1aR) mRNA following experimental manipulation of androgen signalling. We did not find a direct effect of the manipulation on male mating success, paternity or larval production. However, variation in neuroendocrine mechanisms generated by the experimental manipulation was significantly correlated with changes in behaviour and mating success: V1aR expression was negatively correlated with satellite-directed aggression, and expression of its ligand arginine vasotocin (AVT) was positively correlated with courtship and mating success, thus revealing the potential for sexual selection on these mechanisms. © 2018 John Wiley & Sons Ltd
Keywords: 11-ketotestosterone; Androgen Receptor Antagonists; Animals; Brain; Female; Flutamide; Male; Neurosecretory Systems; Perciformes; RNA, Messenger; Receptors, Androgen; Reproduction; Sexual Behavior, Animal; Social Behavior; Spermatozoa; Testosterone; alternative reproductive tactics; androgen receptor; androgen receptor antagonist; androgens; animal; brain; dept.psy; drug effect; female; flutamide; genetics; male; messenger RNA; metabolism; neuroendocrine; neuroendocrine system; peer-reviewed; physiology; reproduction; sexual behavior; sexual selection; social behavior; social behaviour; spermatozoon; teleosts; testosterone

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics. - Nugent, Bridget M.; Stiver, Kelly A.; Alonzo, Suzanne H.; Hofmann, Hans A. (Molecular Ecology, 2016)
The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites and nesting males), which arise from a single genome, have been thoroughly characterized. To determine the neuroendocrine and genomic mechanisms associated with discrete phenotypic variation and ARTs in S. ocellatus in their natural environment, we constructed a whole-brain de novo transcriptome and compared global patterns of gene expression between sexes and male morphs. Next, we quantified circulating cortisol and 11-ketotestosterone (11-kt), mediators of male reproductive behaviours, as well as stress and gonadal steroid hormone receptor expression in the preoptic area, ventral subpallial division of the telencephalon and dorsolateral telencephalon, critical brain regions for social and reproductive behaviours. We found higher levels of 11-kt in nesting males and higher levels of cortisol in sneaker males relative to other male morphs and females. We also identified distinct patterns of brain region-specific hormone receptor expression between males such that most hormone receptors are more highly expressed in satellites and nesting males relative to sneakers and females. Our results establish the neuroendocrine and molecular mechanisms that underlie ARTs in the wild and provide a foundation for experimentally testing hypotheses about the relationship between neuromolecular processes and reproductive success. Copyright © 2016 John Wiley & Sons Ltd.
Keywords: *Neurosecretory Systems/ph [Physiology]; *Perciformes/ph [Physiology]; *Reproduction; *Sexual Behavior, Animal; 11-ketotestosterone; Animals; Brain; Brain/me [Metabolism]; Female; Hydrocortisone; Hydrocortisone/bl [Blood]; Male; Nesting Behavior; Neurosecretory Systems; Perciformes; Perciformes/ge [Genetics]; Phenotype; Reproduction; Sexual Behavior, Animal; Testosterone; Testosterone/aa [Analogs & Derivatives]; Testosterone/bl [Blood]; Transcriptome; alternative reproductive tactics; analogs and derivatives; animal; blood; brain; dept.psy; female; gene expression; genetics; hormones; hydrocortisone; male; metabolism; nesting; neurosecretion; peer-reviewed; phenotype; physiology; reproduction; sexual behavior; testosterone; transcriptome

Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak

Neural gene expression profiles and androgen levels underlie alternative reproductive tactics in the ocellated wrasse, symphodus ocellatus - Stiver, Kelly A.; Harris, Rayna M.; Townsend, Jeffrey P.; Hofmann, Hans A.; Alonzo, Suzanne H. (Ethology, 2014)
Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within-sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between years. Satellites and sneakers spawn parasitically in dominant (nesting) males' nests, but only nesting males provide parental care. Nesting and satellite males show transient cooperative defense of nests against sneakers. Here, we analyze circulating sex steroid hormone levels and neural gene expression profiles in these three male phenotypes and in females. 11-ketotestosterone (but not testosterone) was highest in nesting males, while estradiol was highest in females. Brain transcriptomes of satellites and females were most similar to each other and intermediate to nesting and sneaker males. Sneakers showed more total expression differences, whereas nesting males showed higher magnitude expression differences. Our findings reveal the surprising extent to which neural gene expression patterns vary across reproductive tactics that vary in a number of social traits, including aggression, territoriality, and cooperation, providing important insights into the molecular mechanisms that may underlie variation in cooperative and reproductive behavior. © 2014 Blackwell Verlag GmbH.
Keywords: Androgens; Competition; Cooperation; Mating tactic; Microarray; Reproduction; Symphodus ocellatus; dept.psy

Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H. (Journal of Fish Biology, 2018)
This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full-sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male-controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits. © 2018 The Fisheries Society of the British Isles
Keywords: Animals; Female; Fertilization; Male; Mating Preference, Animal; Paternity; Perciformes; Reproduction; Sexual Behavior, Animal; Symphodus ocellatus; animal; behaviour; dept.psy; female; fertilization; male; mate choice; mating systems; paternity; peer-reviewed; reproduction; sexual behavior; sexual conflict; sexual selection; trade-offs

Ejaculate allocation and sperm characteristics differ among alternative male types in a species of fish with cooperation and competition among unrelated males. - Alonzo, Suzanne H.; Stiver, Kelly A.; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Nugent, Bridget; Kazancıoğlu, Erem (Cells, 2021)
Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete during reproduction. Nesting males build nests, court females and provide care. Sneaker males only “sneak” spawn, while satellite males sneak, but also help by chasing away sneakers. We found that satellite males have larger absolute testes than either sneakers or nesting males, despite their cooperative role. Nesting males invested relatively less in testes than either sneakers or satellites. Though sneakers produced smaller ejaculates than either satellite or nesting males, we found no difference among male types in either sperm cell concentration or sperm number, implying sneakers may produce less seminal fluid. Sperm tail length did not differ significantly among male types, but sneaker sperm cells had significantly larger heads than either satellite or nesting male sperm, consistent with past research showing sneakers produce slower sperm. Our results highlight that social interactions among males can influence sperm and ejaculate production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Animals; Fishes; Male; Reproduction; Spermatozoa; Testis; adult; animal; article; controlled study; court; dept.psy; female; fish; human cell; male; metabolism; nesting; nonhuman; peer-reviewed; phenotypic plasticity; reproduction; seminal plasma; sexual selection; social interaction; sperm competition; sperm count; spermatozoon; spermatozoon tail; testis

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Ocean acidification affects fish spawning but not paternity at CO2 seeps - Milazzo, Marco; Cattano, Carlo; Alonzo, Suzanne H; Foggo, Andrew; Gristina, Michele; Rodolfo-Metalpa, Riccardo; Sinopoli, Mauro; Spatafora, Davide; Stiver, Kelly A; Hall-Spencer, Jason M (Proceedings of the Royal Society B: Biological Sciences, 2016)
Fish exhibit impaired sensory function and altered behaviour at levels of ocean acidification expected to occur owing to anthropogenic carbon dioxide emissions during this century. We provide the first evidence of the effects of ocean acidification on reproductive behaviour of fish in the wild. Satellite and sneaker male ocellated wrasse (Symphodus ocellatus) compete to fertilize eggs guarded by dominant nesting males. Key mating behaviours such as dominant male courtship and nest defence did not differ between sites with ambient versus elevated CO2 concentrations. Dominant males did, however, experience significantly lower rates of pair spawning at elevated CO2 levels. Despite the higher risk of sperm competition found at elevated CO2, we also found a trend of lower satellite and sneaker male paternity at elevated CO2 Given the importance of fish for food security and ecosystem stability, this study highlights the need for targeted research into the effects of rising CO2 levels on patterns of reproduction in wild fish. Copyright © 2016 The Author(s).
Keywords: *Carbon Dioxide/ch [Chemistry]; *Perciformes/ph [Physiology]; *Reproduction/ph [Physiology]; *Seawater/ch [Chemistry]; *Sexual Behavior, Animal; Alternative reproductive tactics; Animals; CO2 vent; Carbon Dioxide; Climate change; Hydrogen-Ion Concentration; Labrid; Labridae; Male; Oceans and Seas; Perciformes; Reproduction; Seawater; Sexual Behavior, Animal; Symphodus ocellatus; acidification; animal; anthropogenic effect; carbon dioxide; carbon emission; chemistry; climate change; concentration (composition); courtship; dept.psy; ecological stability; food security; male; pH; paternity; perciform; physiology; reproduction; reproductive behavior; sea; sea water; sexual behavior; spawning population; sperm competition; wild population